Evaluation of commitment to applying risk management in the events and conferences sector in the Riyadh region, KSA - Alshubaili, Lulu Saud (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to measure the commitment of the management of the events and conferences sector in the Riyadh region using risk management. The inductive qualitative approach was used, and the study tool was the questionnaire using data collected from (152) workers in the Riyadh region in the Kingdom of Saudi Arabia. The results of the study concluded that the degree of applying risk management in the organization of conferences and events was entirely acceptable, and that there were no statistically significant differences at the level of significance (α ≤ 0.05) indicating the degree of application of risk management in the events and conferences sector (Riyadh region) for the variable (the age). While there are statistically significant, differences at the level of significance (α ≤ 0.05) between the degrees of applying risk management in the events and conferences sector (Riyadh region) due to the variable (educational qualification) and in favor of the study individuals whose academic qualifications are (diploma). There are also statistically significant differences at the level of significance (α≤0.05) between the degree of applying risk management in the events and conferences sector (Riyadh region) due to the variable (years of experience) for the benefit of the study individuals who have experience (more than 15 years). The study recommends the importance of increasing supervision over the implementation of the risk management plan in events and conferences, and conveying its understanding to its employees and organizers, and for it to be an essential part of event or conference management, and paying attention to it improves the standing of organized companies with customers, and the most prominent problem facing the research is the lack of knowledge of some workers in this field of the importance of risk management, which makes it difficult to collect information.
Keywords: management; risks; events; conferences; Kingdom Saudi Arabia; Vision 2030